Association of fat mass and obesity-associated (FTO) gene rs9939609 variant with obesity among multi-ethnic Malaysians in Kampar, Perak - Wei, Wei Chey; Sook, Ha Fan; Yee, How Say (Universiti Kebangsaan Malaysia, 2013)
Obesity is a multifactorial disease caused by the interaction of genetic, lifestyle and environmental factors. Common single nucleotide polymorphisms in the recently-described Fat Mass and Obesity-Associated (FTO) gene have been related to body weight and fat mass in humans and genome-wide association studies in several populations have indicated that the FTO rs9939609 variant is associated with obesity. Therefore, the objective of this study was to investigate the association of the FTO rs9939609 variant with obesity among 324 multi-ethnic Malaysians (98 Malays, 158 Chinese, 68 Indians) who attended the Kampar Health Clinic, Perak. With the overall minor A allele frequency (MAF) of 0.199, the distribution of genotypes and alleles was significantly different among ethnicities (MAF highest among Malays), but no association was found for obesity, related anthropometric measurements and gender. Subject with allele A had marginally but significantly higher waist circumference (p=0.015), thus the FTO rs9939609 allele was associated with central obesity (p=0.034 by Chi-square analysis; Odds Ratio (OR)=1.680 (CI=1.036, 2.724; p=0.035)). However, this association was abolished when adjusted for age, gender and ethnicity (OR=1.455, CI=0.874, 2.42; p=0.149). In conclusion, the MAF of the FTO rs9939609 SNP was low as in other Asian populations and there was no evidence for an involvement of this SNP in obesity and obesity-related traits in this multi-ethnic Malaysian study group.